2016
DOI: 10.3390/ijms17081248
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Uric Acid Concentration with Diabetic Retinopathy and Albuminuria in Taiwanese Patients with Type 2 Diabetes Mellitus

Abstract: Patients with type 2 diabetes mellitus (DM) may experience chronic microvascular complications such as diabetic retinopathy (DR) and diabetic nephropathy (DN) during their lifetime. In clinical studies, serum uric acid concentration has been found to be associated with DR and DN. The goal of this study was to evaluate the relationship between the increases in serum uric acid level and the severity of DR and albuminuria in Taiwanese patients with type 2 DM. We recorded serum uric acid concentration, the severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…In this study, SUA was shown to be a risk factor for DR in T2D patients. In addition, this notion was supported by a recent study that the more severe DR, the more elevated level of SUA [6]. These findings are consistent with the previous studies by Lee et al 2014 andFukui et al 2008 [7,8].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, SUA was shown to be a risk factor for DR in T2D patients. In addition, this notion was supported by a recent study that the more severe DR, the more elevated level of SUA [6]. These findings are consistent with the previous studies by Lee et al 2014 andFukui et al 2008 [7,8].…”
Section: Discussionsupporting
confidence: 91%
“…HG group, cells incubated in DMEM/HG medium; HG+UA group, cells incubated in UA (10mg/dl) added to DMEM/HG medium; HG+ HUA+EMP group, cells incubated in DMEM/HG medium with UA (10mg/dl) and treated with 50 μM empagliflozin; HG+UA+ Compound C group, cells incubated in DMEM/HG medium with UA (10mg/dl) , AMPK inhibitor Compound C (10μM) and empagliflozin (50 μM) for 48 hours. HUA carries a significant risk for developing various diseases in T2DM [4][5][6][7][8], therefore, exploring the metabolism of UA and associated diseases has attracted researchers' much attention. However, it is a challenge to create hyperuricemic models in mice, because in rodents, uricase oxidizes UA to allantoin which is highly soluble in water and excreted unchanged in the urine, but not in humans [24].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have indicated that incidence of HUA in patients with T2DM was respectively 24.1% [2] and 33.8% [3]. Moreover, HUA has proven to be an independent risk factor for kidney disease progression [4,5], and significantly correlated with the severity of retinopathy in patients with T2DM [6]. Accumulating data has indicated that HUA was closely associated with risks of increased prevalence of cardiovascular disease [2,4], carotid intima-media thickness [7], hypertension [8] and metabolic syndrome [8] in individuals with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…17 A study conducted by Ching-Chao Liang et al, concluded that there were increased serum uric acid levels which correlated with the severity of diabetic Retinopathy in patients with type 2 DM. 18 Vitreous UA and glucose concentrations were higher in proliferative than in non-proliferative DR. Focal UA production in the vitreous is thought to be involved in the pathogenesis and progression of DR. 19 UA is lowered in Diabetes mellitus (DM) due to hyperfiltration 20 , but decreased UA excretion during renal dysfunction raises SUA levels. Nazir Shah et al 21 conducted a study in 2013 in 163 patients of diabetes mellitus (type 2) and proposed that elevation in the levels of uric acid was more in the diabetic patients with nephropathy (50%).…”
Section: Discussionmentioning
confidence: 86%